Prevalensi Dermatitis Kontak di Satuan Medis Fungsional Kulit dan Kelamin RSUP. H. Adam Malik Periode Januari 2010 – Desember 2010 - Nopa, Ika (Universitas Muhammadiyah Sumatera Utara, 2019)
Contact dermatitis is a dermatitis caused by the material or substance that sticks to the skin. Data from NIOSH found from 372,000 work-related illness were reported 12% is a skin disease or disorder and 80% of occupational skin disease is contact dermatitis. To observe the progression of this disease, therefore a research was conducted to observe the latest prevalence of contact dermatitis.The purpose of this research is to find out the prevalence of contact dermatitis at Dermatology Polyclinik of Haji Adam Malik General Hospital, Medan in January 2010 -December 2010. This is a descriptive study and the design is cross-sectional study. Population in this research was all medical records of contact dermatitis from January 2010 - December 2010, and samples were taken by simple random sampling method and 97 medical records sampled. All the collected data were calculated with SPSS and presented in distribution tables.Results showed the prevalence of contact dermatitis patients is 660 patients (11.65%) of the entire population, with the highest percentage found in the female as many as 62 patients (63.9%) of the sample. Based on age group, the highest prevalence found in 30-39 years old as many as 28 patients (28.9%) of the sample. Based on the type of work, the highest prevalence found in housewives as many as 31 patients (32%) of the sample. Based on the location of contact dermatitis, the highest prevalence found in the hands of the 35 patients (36.1%) of the sample. Based on the type of work, location of most lesions on housewives found on the hand, and that 18 of 31 patients.